Genetic privacy : a challenge to medico-legal norms - Laurie, G. T. (Graeme T.) (Cambridge University Press, 2002)
The phenomenon of the New Genetics raises complex social problems, particularly those of privacy. This book offers ethical and legal perspectives on the questions of a right to know and not to know genetic information from the standpoint of individuals, their relatives, employers, insurers and the state. Graeme Laurie provides a unique definition of privacy, including a concept of property rights in the person, and argues for stronger legal protection of privacy in the shadow of developments in human genetics. He challenges the role and the limits of established principles in medical law and ethics, including respect for patient autonomy and confidentiality.